Sintesis Magnetite/Hidroksiapatit Composite Menggunakan Metode Presipitasi Dengan Variasi Magnetite Dan Suhu Pemanasan - Wiriyan Jordy; Ahmad Fadli; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Technologies in era of globalization had been improved especially for human health in biomedical. Magnetite/Hydroxyapatite composite is one of new promising idea as drug carrier for a drug delivery application. The purpose of this research is synthesis of the composite by using magnetite & hydroxyapatite, and analyze the effect of percentage of Fe and heating temperature to the characteristic of the composite were produced by using precipitation method. The powder of magnetite was dispersed in 50 ml of aquadest and mixed with Ca(NO3)2.4H2O for 30 minutes, and (NH4)2HPO4 added to the suspense. The pH of suspension was controlled by added NH4OH 25% until pH 11 with reaction for 120 minutes at 90ºC. The suspension was aged for 1 day, washed and separated the precipitated from suspense. The precipitate was dried until 1 day at 70ºC and ended with calcined the precipitate for 3 hours at 400ºC until powder of composite was collected. The powder of composite was characterized with XRD, and VSM. The higher heating temperature to 90ºC had affected higher crystallinity from 80.68% to 86.58%. However, the higher percentage of Fe had affected the crystal size of magnetite from 14.744 nm to 19.894 nm, with a good magnetization value was 8.81 emu/g. Based on the resulted from characterized of the composite, were concluded for the synthesis of composite magnetite/hydroxyapatite were succeeded and can be applied as a drug carrier in the drug delivery system. Keywords : composite, drug carrier, hydroxyapatite magnetite.